RAGAM GRAMATIKAL DALAM ARTIKEL ILMIAH (ACADEMIC VOICES) DI E-JOURNAL - Hafidz, Moh. (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2018)
Grammatical or sound variety in scientific writing (Academic Voices) is a method used by writers to convey their own ideas and other people's ideas in the standard of scientific writing both in the form of Writer's Voice, Direct Voice, Voice indirect (Indirect Voice), additional voice (External Voice). The purpose of this study is to improve the ability of writers about quotations, to distinguish writers' voice, direct voice, indirect voice and external voice and reduce the level of plagiarism in writing journal articles. This study uses research in the form of Electronic Literature Study (E-Library Research) using observation and documentation. The result is 90% (ninety percent) of authors use author's voice (Writer's Voice) rather than direct voice (Direct Voice), indirect voice (Indirect Voice), additional voice (External Voice) in E-journal, formality of writing style scientific works are very varied and e-mail address (e-mail) is one of the conditions for the publication of articles as scientific papers.